Effect of lactobionic acid on the acidification, rheological properties and aroma release of dairy gels. (15th September 2016) - Ribeiro, Jéssica C. Bigaski; Granato, Daniel; Masson, Maria Lucia; Andriot, Isabelle; Mosca, Ana Carolina; Salles, Christian; Guichard, Elisabeth
Highlights: Gels produced with lactobionic acid were less firm than with gluconolactone. No significant difference in sodium ion mobility between LBA and GDL. Lactobionic acid can be used to replace gluconolactone in dairy gels. Abstract: The food industry is investigating new technological applications of lactobionic acid (LBA). In the current work, the effect of lactobionic acid on the acidification of dairy gels (pH 5.5 and 6.2), rheological properties using a double compression test, sodium mobility using 23 Na NMR technique and aroma release using headspace GC–FID were studied. Our results showed that it is possible to use LBA as an alternative to glucono-δ-lactone (GDL) for the production of dairy gels with a controlled pH value. Small differences in the rheological properties and in the amount of aroma volatile organic compounds that were released in the vapour phase, but no significant difference in the sodium ion mobility were obtained. The gels produced with LBA were less firm and released less volatile aroma compounds than the gels produced with GDL. The gels at pH 6.2 were firmer than those at pH 5.5 and had a more organised structure around the sodium ions.